Shade or light? : size class distribution and δ¹³C values as clues to the recruiting environment of Widdringtonia whytei - Mitrani, Leila Mical (Department of Biological Sciences, 2017)
In order to determine the recruitment environment of the endangered Mulanje Cedar, Widdringtonia whytei, size class distributions were measured for six populations on Mount Mulanje, Malawi. Carbon isotope ratios were also collected from leaf tissue in trees of varying height in order to determine the effects of positioning within or below the canopy. Carbon isotope ratios were also taken from wood cores and the δ¹³Cvalues for the innermost and outermost wood were compared for two sites. Size class :frequency distributions had a tendency to be normally distributed but one site showed skewed values towards seedling and another showed a flat distribution, possibly due to continual logging of the trees. Height correlated well with leaf δ¹³Cvalues. Sombani and Bvunje showed the same current (outer wood) δ¹³Cvalues but different recruitment (inner wood) δ¹³Cvalues. Results indicate that Bvunje trees recruited in the shade and Sombani recruited in the sunlight. There is ambiguity in both size class data and carbon isotope data and therefore either Widdringtonia whytei is able to recruit in a variety of manners and environments or other factors are influencing the results.